Krzysztof Zamorski’s Microhistorical Perspective as One of the Ways of Understanding Old Polish Society - Glabisz, Grzegorz (Sensus Historiae, 2025)
This article discusses Krzysztof Zamorski’s book Pleban i wieś. Historia życia proboszcza tenczyńskiego z początków XVIII wieku. Studium mikrohistoryczne as an important contribution both to the study of Old Polish society and to broader reflection on the possibilities of microhistory. I argue that Zamorski goes beyond the reconstruction of an individual life and, through the story of Father Krzysztof Michał Świątecki, reveals the complex web of social, economic, and religious relations that shaped the functioning of a rural parish in the early eighteenth century. The chief strength of the book lies in its ability to combine a biographical approach with an analysis of the wider mechanisms of collective life. I also suggest that the narrative form adopted by Zamorski should not be seen merely as a stylistic choice, but rather as an expression of a distinct methodological position. It is grounded in an attempt to capture historical experience as closely as possible while maintaining strict source criticism and an awareness of the limits of historical interpretation. At the same time, I show that the book represents a strand of microhistory that values scholarly discipline and interpretive restraint more highly than the compelling fictionalization of the past. Particular attention is paid to Zamorski’s scholarly method and to the breadth of his source base, which includes ego-documents, ecclesiastical and court records, as well as economic documentation. This allows him to reconstruct not only the biography of his protagonist, but also the material, institutional, and communal framework within which the local world operated. The parish thus emerges as a space where religious norms, economic interests, and everyday social practices intersect. I also identify the sections devoted to the plague epidemic as especially significant, since they expose the mechanisms through which the community functioned under extreme conditions and illuminate the tensions between duty, fear, and the logic of survival. I conclude that Pleban i wieś is a methodologically self-aware, empirically grounded, and valuable contribution to further research on the social history of the Polish-Lithuanian Commonwealth.